Advanced Virgo Plus: Future Perspectives. Issue 1 (1st January 2023) - Acernese, F; Agathos, M; Ain, A; Albanesi, S; Alléné, C; Allocca, A; Amato, A; Andia, M; Andrade, T; Andres, N; Andrés-Carcasona, M; Andrić, T; et al.
Abstract: While completing the commissioning phase to prepare the Virgo interferometer for the next joint Observation Run (O4), the Virgo collaboration is also finalizing the design of the next upgrades to the detector to be employed in the following Observation Run (O5). The major upgrade will concern decreasing the thermal noise limit, which will imply using very large test masses and increased laser beam size. But this will not be the only upgrade to be implemented in the break between the O4 and O5 observation runs to increase the Virgo detector strain sensitivity. The paper will cover the challenges linked to this upgrade and implications on the detector's reach and observational potential, reflecting the talk given at 12th Cosmic Ray International Seminar - CRIS 2022 held in September 2022 in Napoli.